1987
DOI: 10.1007/bf00452210
|View full text |Cite
|
Sign up to set email alerts
|

The quadriceps function in patellofemoral disorders

Abstract: The influence of quadriceps contraction on patellar alignment was investigated in tangential views of 31 patients with patellofemoral complaints and compared with 25 controls. The congruence angle decreased significantly following quadriceps contraction in patients with patellar subluxation in contrast to those with chondromalacia and normals. Electromyography (EMG) of the vastus lateralis (VL) and vastus medialis obliquus (VMO) during maximal quadriceps contraction was obtained prior to and after 3 months of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Strengthening of the vastus medialis obliquus muscle is considered one of the essential components of the nonoperative approach to patellofemoral pain. 16,34,38,40,43,52,53 Recent studies have concluded that not only the strength of this muscle but also the time to activation is disturbed in patients with patellofemoral pain. 60,65 These studies have also shown that the activation pattern of the vastus medialis obliquus and vastus lateralis muscles is disturbed in patients with patellofemoral pain.…”
Section: Discussionmentioning
confidence: 99%
“…Strengthening of the vastus medialis obliquus muscle is considered one of the essential components of the nonoperative approach to patellofemoral pain. 16,34,38,40,43,52,53 Recent studies have concluded that not only the strength of this muscle but also the time to activation is disturbed in patients with patellofemoral pain. 60,65 These studies have also shown that the activation pattern of the vastus medialis obliquus and vastus lateralis muscles is disturbed in patients with patellofemoral pain.…”
Section: Discussionmentioning
confidence: 99%
“…16,34,38,40,43,52,53 Recent studies have concluded that not only the strength of this muscle but also the time to activation is disturbed in patients with patellofemoral pain. 60,65 These studies have also shown that the activation pattern of the vastus medialis obliquus and vastus lateralis muscles is disturbed in patients with patellofemoral pain.…”
Section: Discussionmentioning
confidence: 99%
“…Two among several EMG studies attempted to investigate patellar location changes resulting from quadriceps contraction [16,27], but both of them utilized conventional imaging techniques under static conditions. There are several studies focused on the relative activity of quadriceps components under different contraction patterns and exercises [4,12,19,32,34,40].…”
Section: Discussionmentioning
confidence: 99%
“…and balanced activity between these two muscles is considered desirable to maintain normal patellofemoral tracking [4,12,19,32,34]. VMO weakness in patellofemoral pain syndrome, patellar instability and effused knees in which imbalanced activity of the VMO and VL has been demonstrated has been noted by several authors [4,18,23,27,[34][35][36]40]. Treatment regimens on the basis of selective strengthening of VMO have had some successful results, but there is still no consensus on whether these contraction patterns also restore the patellofemoral malalignment [16,21,31,38].…”
mentioning
confidence: 99%
See 1 more Smart Citation